Case Report: Penile hamartoma with penile torsion in a child: etiology-targeted one-stage surgical correction and literature review - Yao, Zhigang; Zhanghuang, Chenghao; Zhou, Nian; Li, Jinrong; Hao, Zipeng; Yan, Bing; Zhao, Hui (Frontiers in Pediatrics, 2025)
BackgroundPediatric penile hamartoma is extremely rare. Preoperative imaging often cannot definitively characterize the lesion, and histopathology remains the diagnostic gold standard. We report a child with penile hamartoma and torsion, discuss management, and compare outcomes with the literature.MethodsWe retrospectively analyzed the clinical presentation, imaging, intraoperative findings, and pathology. Relevant reports were reviewed for comparison.ResultsComplete excision of a ventral hamartomatous appendage plus circumcision and release of a fibrous tethering band achieved immediate torsion correction in a single stage. Histopathology showed stratified squamous epithelium with proliferative fibrous and adipose tissue containing nerve bundles, ganglion cells, and focal smooth muscle—consistent with hamartoma. Recovery was uneventful; at 12 months no recurrence was observed.ConclusionEtiology-targeted, one-stage correction—degloving (circumcision), release of tethering bands, complete lesion excision, and simultaneous torsion repair—can be safe and effective. Long-term follow-up is advised.